Sifat Mekanik dan Struktur Mikro Magnet Komposit Campuran Resiprene 35 Barium Ferit Dengan Resin Epoksi. - Bunga Fisikanta Bukit; Nurdin Bukit; Ferry R.A Bukit (JUITECH: Jurnal Ilmiah Fakultas Teknik Universitas Quality, 2020)
A composite composite of Resiprene 35 and barium ferrite was made with Epoxy resin. This study aims to determine the mechanical properties (tensile strength, modulus of elacity, strain and flexural strength) and the magnetic microstructure of the resulting composite. The manufacturing method is carried out by mixing Resiprene 35 solution with and barium Ferrit with Epoxy resin with various variations in the ratio of (2.5: 2.5: 95)%, (5: 5: 90)% and (10:10:80)% with the leaky mold method. From the test results obtained a composite magnet that has the greatest tensile strength is a composite magnet at a mass fraction ratio (5: 5: 90)%, with an average maximum stress of 18.19 MPa and an average maximum strain of 4.79% and an average maximum modulus of elasticity an average of 1.86 MPa. Composite magnets that have the greatest flexural strength are composite magnets at a mass fraction ratio (5: 5: 90)%, with an average maximum flexural strength of 51.00 MPa and an average maximum deflection of 10.61 mm. as well as the composite morphological analysis of the mass fraction (5: 5: 95)%, it appears that resiprene 35 and barium ferrite have been strongly bonded with epoxy and homogeneous resins